Macroeconomic transformation of capitalism - How to achieve politically determined growth rates? - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
An economy with a stable medium-term growth rate of zero - or any other politically determined growth rate - needs new regulations and institutions to realise this target. Such an economy would look very different compared with the existing type of capitalism we have today in the Global North. In the existing capitalist system, investment demand as well as autonomous demand elements like government demand, export demand or autonomous consumption demand drive the dynamic of GDP and the whole economic system. In a zero growth economy the different demand aggregates are determined by economic policy including heavy intervention in income and wealth distribution and the direction of technological development. Whether such an alternative system is understood as a version of highly regulated capitalism or as a new system is a question of taste.
Keywords: B20; B52; P41; 330; Transformation of capitalism; economic systems; zero growth